Management Strategies for Information Technology - Earl Michael J (Prentice Hall, 1989)
This book examines how information technology has become a strategic issue for many organizations and shows how IT can be exploited for strategic advantage. Preface, The IT Era, Information Management, Information Technology and Strategic Advantage, Formulating Information Systems Strategy, Formulating IT Strategy, Formulating IM Strategy, Organizing IT Activities, Controlling IT Activities, Change Strategies for Strategic Change, Index.